Exploring the Effects of LED Lighting Training Program on Motor Performance among Young Athletes. Issue 1 (2nd January 2021) - Arede, Jorge; Carvalho, Márcio; Esteves, Pedro; de las Heras, Bernat; Leite, Nuno
ABSTRACT: The aim of this study was to examine the effects of a BATAK Pro™ training program in combination with regular sport-specific training as compared with sport-specific training alone on motor performance among young athletes. Twenty-two athletes (aged 11–16 years) were recruited and randomly assigned to either an active control group or BATAK training group. The BATAK training program consisted of 2–3 sets of 4–5 exercises, biweekly for 12-weeks. The assessment of motor performance included upper limb movement speed, agility, reactive agility, acceleration, sprinting, and Y-Balance test. Within-group analyses revealed performance increases in the 10-m sprint test (−2.6%), and in Y-Balance test variables, specifically in anterior direction (4.0–5.4%), posteromedial direction (6.6–8.0%) and in posterolateral direction (10.7–14.6%) in the BATAK group. This study reports for the first time that the use of LED lighting devices in addition to sport-specific training promotes increases in motor skills, particularly in dynamic stability. More studies are needed to confirm whether the training-induced benefits of this novel performance tool are significantly better as compared to other approaches, and whether these results can be translated into on-field performance outcomes, not only in terms of critical motor development but also in a meaningful increase of creative actions.